Challenges in the Substitution of Terminal C–C Double Bonds with Tertiary Alkyl groups - Nishikata, Takashi; Ishikawa, Shingo (Synlett, 2015)
There are a few reports on the reaction of tertiary alkyl halide and alkene to produce an alkyl-substituted alkene. To establish tertiary alkylation of a C–C double bond, radical reaction is found to be one of the most promising protocols. In this paper, we highlight tertiary alkyl substitutions on C–C double bonds via atom-transfer radical substitution (ATRS) catalyzed by a copper salt and introduce the corresponding M–H reactions.1 Alkylation via the Mizoroki–Heck Reaction2 Tertiary Alkylative M–H-Type Reaction3 Regioselective Double-Bond Formation4 Summary and Perspectives
Keywords: copper; radical; tertiary alkylation; Heck; alkene